2007
DOI: 10.1016/j.trstmh.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Heavy cryptosporidial infections in children in northeast Brazil: comparison of Cryptosporidium hominis and Cryptosporidium parvum

Abstract: Cryptosporidium is an important cause of infectious diarrhoea worldwide, but little is known about the course of illness when infected with different species. Over a period of 5 years, Cryptosporidium was identified in the stools of 58 of 157 children prospectively followed from birth in an urban slum (favela) in northeast Brazil. Forty isolates were available for quantification and 42 for speciation (24 Cryptosporidium hominis and 18 C. parvum). Children with C. hominis shed significantly more oocysts/ml of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
2
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 25 publications
5
65
2
11
Order By: Relevance
“…4,28,32 In a longitudinal study from Brazil, C. hominis and C. parvum infections were associated with decrease in HAZ scores within three months postinfection but this decrease was found to persist at 3-6 months after C. hominis infections, but not C. parvum infections. 35 Low birth weight, malnutrition, stunting and lack of breastfeeding have been reported to predispose children to cryptosporidiosis. 2,4,30 In this birth cohort, the median age of weaning was three months (IQR = 1.8-4 months).…”
Section: Discussionmentioning
confidence: 99%
“…4,28,32 In a longitudinal study from Brazil, C. hominis and C. parvum infections were associated with decrease in HAZ scores within three months postinfection but this decrease was found to persist at 3-6 months after C. hominis infections, but not C. parvum infections. 35 Low birth weight, malnutrition, stunting and lack of breastfeeding have been reported to predispose children to cryptosporidiosis. 2,4,30 In this birth cohort, the median age of weaning was three months (IQR = 1.8-4 months).…”
Section: Discussionmentioning
confidence: 99%
“…C. hominis, which is associated with a longer duration of symptoms and oocyst shedding, leads to more severe clinical features in humans rather than C. parvum. Additionally, C. hominis infections have been reported to be seen in children, while C. parvum affects adults (12,31,32). It has also been presented that clinical and pathological characteristics can vary depending on the subtypes of the agent, and some C. hominis subtypes, such as subtype Ib identified by GP60 sequence, may cause severe diarrhea accompanied by vomiting and malaise (3,27).…”
Section: Discussionmentioning
confidence: 99%
“…In studies that discuss the molecular characterization of feces samples testing positive for Cryptosporidium spp., C. hominis was detected at a frequency of 40-90% in HIV-positive patients and 57.1-73.6% in children. In contrast, C. parvum frequency ranged from 10% to 20% in HIV-positive patients and from 10.5% to 42.9% in children (GONÇALVES et al, 2006;BUSHEN et al, 2007;ARAÚJO et al, 2008;LUCCA et al, 2009;ROLANDO et al, 2012).…”
Section: Epidemiological Aspects Of Human Cryptosporidiosismentioning
confidence: 97%
“…Studies on dairy farms have shown that C. parvum was more frequent in calves up to 2 months of age; C. bovis and C. ryanae, in older calves and steers; and C. andersoni, in steers and adults (SANTÍN et al, 2004;FAYER et al, 2007;SANTÍN et al, 2008). Despite the low prevalence of C. parvum in steers and adults, some studies have identified this species in this age group (FAYER et al, 2007;BUDU-AMOAKO et al, 2012;WELLS et al, 2015).…”
Section: Epidemiological Aspects Of Bovine Cryptosporidiosismentioning
confidence: 99%
See 1 more Smart Citation